Contestation between Fiqh and Culture in Indonesia: The Maqāṣid al-Sharī’ah Paradigm in Dangers of Forced Marriage against Women - Arifah Millati Agustina (Sawwa: Jurnal Studi Gender, 2023)
This article addresses the contentious issues between Islamic Jurisprudence (fiqh) and cultural practices related to forced marriage. Motivated by the widespread prevalence of forced marriage in society, often perpetuated with religious arguments, the research aims to provide insights into the meaning of the term “ijbar” in fiqh discourse. While fiqh interprets “ijbar” as a custodian’s right to coerce their daughter, the article highlights the specific term “ikrah” for coercion in Islamic law. Utilizing a qualitative method, the study involves document analysis through an in-depth examination of fiqh literature. Data sources include classical and contemporary jurisprudence literature, information on forced marriages in Indonesia, and religious fatwas from the Indonesian Women’s Ulama Congress (KUPI). The article argues that forced marriage contradicts the maqāṣid al-sharī'ah, evidenced by spiritual and religious decline, domestic violence, restricted access to education, adverse reproductive effects, and limited economic resources.